2006
DOI: 10.3402/ijch.v65i1.17876
|View full text |Cite
|
Sign up to set email alerts
|

Violent deaths in small children in northern Sweden

Abstract: Objectives. To identify causes and trends of violent deaths among children younger than 4 years in a northern region. Study design. Retrospective analysis of medico-legal autopsy and police data. Methods. Data from all 72 deaths from "external causes " 1977-2004, in children < 4 years from the northern half of Sweden were analysed. Results. The death rate was 7.1 per 100,000 children and year during the first half of the study period, and 5.2 during the second half. Vehicle-and drowning-related deaths were hal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 36 publications
0
3
0
1
Order By: Relevance
“…The information on intentional deaths in infancy is scarce. However, several authors emphasize that infants are at increased risk of being battered to death [17,18]. Another concern is that in case of further 27.6% of infant deaths the manner of death was undetermined which raises suspicion about considerable underestimation of infanticide in Estonia.…”
Section: Discussionmentioning
confidence: 99%
“…The information on intentional deaths in infancy is scarce. However, several authors emphasize that infants are at increased risk of being battered to death [17,18]. Another concern is that in case of further 27.6% of infant deaths the manner of death was undetermined which raises suspicion about considerable underestimation of infanticide in Estonia.…”
Section: Discussionmentioning
confidence: 99%
“…Only a few generations back the greatest dangers were faced out on the land, and most often away from the camp or village – in an overturned qayaq (kayak) at sea, a sudden white-out (blizzard) on the tundra, or a patch of rotten ice that gives way during a river crossing. Now young people are instead much more likely to face their greatest dangers at home, at school, or somewhere else within the confines of the village community – in a drinking parent or relative, a jealous friend, or their own suicidal urges (Gessner, 1997; Kettl & Bixler, 1993; Wexler & Goodwin, 2006). These new experiences in the lives of youth are products of a relatively recent colonial history in Alaska.…”
mentioning
confidence: 99%
“…When the data related with 72 deaths which occurred as a result of external causes between 1977 and 2004 in young children below the age of four years in Sweden were examined, it was found that 15 (21%) occurred as a result of crashing of motor vehicles and 14 (19%) occurred as a result of in-vehicle accidents. In twelve children (17%), the reason was found to be intentional assault (15). When all injuries-deaths between the ages of zero and 17 years between 2000 and 2006 in San Diego County, California were examined, it was found that 884 legal medical examinations was performed and death occurred because of unnatural reasons in 480 of these.…”
Section: Discussionmentioning
confidence: 99%